Caracterização limnológica e contaminação de peixes por cádmio na bacia do Ribeirão Cambé (Londrina-PR) - Damasio, Barbara Cristina Reis (2018)
The Ribeirão Cambé Basin (Londrina-PR), has suffered from anthropic action, especially due to the presence of trace elements from industrial and urban sources. The objective of this study was to characterize lomnologically temperature, pH, turbidity, electrical conductivity and dissolved oxygen of Ribeirão Cambé and to analyse concentration of Cadmium (Cd) contaminant in fish species at all collection points from 2013 to 2015. Six sampling points were selected and the manual and electrical fishing were applied to fish samples with a sampling effort of 40 minutes each. After collect, the whole individuals were dried, sieved and prepared with an acid solution of nitric acid with hydrogen peroxide for digestion. For the detection of the metals in the fish samples the technique of Inductively Coupled Plasma Mass Spectrometry and Graphite Furnace Atomic Absorption Spectrometry was used. The results of the limnological parameters of water revealed values that exceeded the limits allowed by Conama Resolution 357/2005 and CETESB. The parameter dissolved oxygen had values below the allowed limit of 6 mg/L in points 1, 3 and 5 indicating a possible pollution of the water body in these places. The electrical conductivity presented values above the allowed limit of 100 μS/cm in all six sampling points. The two largest accumulated means of 277 and 356 μS/cm were found, respectively, in points 3 and 6 indicating highly impacted environments. The parameters of water temperature, turbidity and pH were within the limit allowed for all sampling points. A total of 803 individuals belonging to four genera and eleven different species were collected. The results showed a high concentration of cadmium in fish species along the riverside above de limit established by Resolution RDC N°42 on Maximum Limits of Inorganic Contaminants in Foods. Point 5 was the most prominent, presenting high concentrations of the metal in two species of Hypostomus (suckermouth catfish) in all periods of collection. Points 3 and 4 located in Lake Igapó also out showing high concentrations of the metal in the species Tilapia rendalli and Oreochromis niloticus frequently consumed by individuals who practice amateur fishing in these two places in all the collection periods, excepts in the collection made in the winter of 2015. The results of this work reveal the urgent need to implement a program to monitor the contamination of the waters of Ribeirão Cambé by metals, evaluating in more detail its implications for the health of the population.